Contested geopolitical messages for tourists at the Okinawa Peace Park and memorials. Issue 3 (3rd July 2019) - Hashimoto, Atsuko; Telfer, David J.
Abstract: Now marketed as a tropical beach destination, Okinawa's identity is also forever linked with the horrors of war. Okinawa's tumultuous past encompasses the Ryukyu Islands, which had close economic ties to China until being annexed by mainland Japan, were invaded by the US in the Second World War, were occupied until 1972 and, more recently, have become the centre of heated debates over the continued presence of US military bases. The Battle of Okinawa was one of the bloodiest of the Second World War and the inhabitants faced not only the American invasion but also the tactics of the Japanese army, who viewed the islands as expendable in order to slow invading forces from reaching mainland Japan. In the context of the seventieth anniversary of the end of the Battle of Okinawa in 2015, and beyond, it is argued here that these conflicting geopolitical disputes present significant challenges in terms of the messages presented to educational dark tourists visiting the Okinawa Peace Park and Memorials. The Peace Park Story Tellers or kataribe who are the Second World War survivors, have the critical task of mediating the message to both domestic and international tourists, some of whom are not prepared to hear anti-Japan sentiment. Through an examination of the historical and geographic background, and an analysis of the tourist experience at the Peace Park and Memorials, this paper explores the complexity of educational dark tourism where competing messages collide.